In – vitro anti tubercular activity of flowers of Couroupita guanensis L - Aravind, D Sai; Karthikeyan, R; Babu, P Srinivas (Creative Pharma Assent, 2017)
Modern civilization is facing hundreds of disorders associated with microorganisms. The natural phytochemicals from non-edible plants are gaining importance to fight against these disease The intention of this study is to evaluate the ethanol and dichloromethane extracts of flower of Couroupita guianensis (Lecithydaceae) for anti-tubercular activity. The anti-tubercular activity of all the extracts of Couroupita guianensishave been evaluated against Mycobacterium tuberculosis H73Rv strain using Microplate Alamar Blue Assay (MABA). The activity was documented within MIC range of 0.8 to 100μg/ml. The results of MABA showed that both ethanol and dichloromethane extract exhibited significant anti-tubercular activity. The present investigation suggests that Couroupita guianensis possess remarkable anti-tubercular activity